T221. CAUSAL RELATIONSHIPS BETWEEN EMPATHY, MOTIVATION AND FUNCTIONAL OUTCOMES IN EARLY SCHIZOPHRENIA IDENTIFIED WITH CAUSAL DISCOVERY MODELING. (18th May 2020) - Miley, Kathleen; Vinogradov, Sophia; Meyer-Kalos, Piper; Kummerfeld, Erich
Abstract: Background: Schizophrenia is characterized by devastating impairments in occupational and social functioning. These impairments result in poor quality of life, have significant societal burden, and are resistant to current treatments. Although a number of predictors of poor functional outcomes have been identified, the causal relationships between malleable illness variables and functional status must be discovered to establish the most promising candidate treatment targets. The aim of this research is to employ a data-driven causal network approach in the Recovery After an Initial Schizophrenia Episode (RAISE) trial to identify variables that have causal effects on occupational and social functioning. Our second aim was to validate our results in an independent sample drawn from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study. Methods: Measures of neurocognition, motivation, empathy, psychiatric symptoms, duration of untreated psychosis, and social and occupational functioning were obtained for 279 participants with early schizophrenia enrolled in RAISE. Data were analyzed using a machine learning causal discovery algorithm, Greedy Fast Causal Inference, which infers causal relationships among the variables while identifying potential influences of latent variables. Causal effect sizes (ES) were estimated by fitting a linear structural equation model to the causal graph. Graph stability was evaluated by running GFCI on 1000 jackknifed and 1000 bootstrapped datasets. Results were validated using a similar set of variables in 187 participants in the CATIE study who were within five years of initiating antipsychotic treatment. Results: Baseline empathy caused baseline motivation (ES = 0.77), which in turn caused both baseline social (ES = 1.5) and occupational (ES = 0.96) functioning. Baseline social and occupational functioning then caused six-month social and occupational functioning, respectively. Additionally, at the six-month time point, social functioning caused motivation (ES = 0.21), which in turn caused occupational functioning (ES = .92). Causal relationships between motivation and social functioning were cyclical through time. The causal structure in the CATIE dataset had some less determinate edge orientations, but otherwise confirmed the findings from RAISE. The jackknife and bootstrap causal graphs showed high concordance with all graph features in the social and occupational functioning subgraphs. Discussion: Motivation and empathy at baseline have causal effects on both occupational and social functioning six months after entering treatment in early schizophrenia. In addition, an improvement in social functioning over six-months may drive improvements in occupational functioning. This indicates that future research should test the efficacy of interventions targeting motivation and empathy for promoting functional recovery in early schizophrenia as soon as individuals enter treatment.